Ayurvedic Management of Endometrial Hyperplasia - A Case Report - Anila. M; Drishya. P. T; Jyothi. P. K (International Journal of Ayurveda and Pharma Research, 2021)
Abnormal uterine bleeding is the changes in frequency of menses, duration of flow or amount of blood loss. AUB affects 1/3 of the women of child bearing age. Increased endometrial thickness is a common cause of abnormal uterine bleeding. Unopposed action of estrogen on endometrial tissue cause endometrial hyperplasia. Heavy menstrual bleeding is the main clinical feature of this condition. Premenopausal period is more susceptible to hyperplasia of endometrium. Atypical type of endometrial hyperplasia may lead to endometrial cancer. Medical management with correction of hormone imbalance is the first line of treatment. According to Ayurveda Asrugdara is a condition where there is occurrence of heavy menstrual bleeding. Excess intake of food which are Lavana (salt), Amla (sour), Guru (heavy) Teekshna (pungent) and Snigda (unctuous) etc leads to this condition. There are 4 types Asrugdara. The nature of menstrual bleeding in Kaphaja Asrugdara is Guru (heavy), Seetalam (cold) and Ghanam (dense). In Paithika asrugdara there is excess menstrual bleeding. This is the case report of 40 yr old female subject who came to the OPD of Prasutitantra and streeroga, Govt. Ayurveda college Thiruvananthapuram with complaints of irregular and heavy menstrual bleeding. She had undergone allopathic management both medical and surgical. Her endometrial thickness was 19mm at commencement of treatment. The condition at that time had features of Kapha paithika asrugdara and hence treatment principle of Kapha paithika asrugdara were applied here. The patient got considerable relief in clinical features, reduced number of pads from 15-18/day to 3 pads/day and her duration got reduced from 35 days to 3 days. Hence appropriate Ayurvedic management for Asrugdara with due consideration to Doshas can be effective in conditions like endometrial hyperplasia.